2020
DOI: 10.3390/su12104093
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Assessment of Sustainability Traits in Meat Production. A Choice Experiment Study in Spain

Abstract: Consumers are increasingly concerned about the way their food is produced. This is particularly relevant in the case of meat, due to the impacts that its production methods can have on greenhouse gas emissions and its role in climate change. In relation to this issue, the purpose of our research is to obtain more information on the consumer decision-making process for beef, in order to determine the relative importance of sustainability claims and traditional attributes, and identify consumer profiles with sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 89 publications
(115 reference statements)
1
22
0
2
Order By: Relevance
“…Concern for the environment is growing among young people, and environmental awareness has been pinpointed as the most important feature identifying the millennial generation (Eldesouky et al, 2020;Thach and Olsen, 2006). In this direction, another study has underlined the function of the wording on labels, highlighting the importance given to terms such as: eco-friendly, recycled and "green"; all these terms seem to positively influence the perception of millennials, increasing the reputation of the producer (Annunziata et al, 2019;Smith, 2010).…”
Section: Environmentally Friendly and Sustainable Food Consumptionmentioning
confidence: 99%
“…Concern for the environment is growing among young people, and environmental awareness has been pinpointed as the most important feature identifying the millennial generation (Eldesouky et al, 2020;Thach and Olsen, 2006). In this direction, another study has underlined the function of the wording on labels, highlighting the importance given to terms such as: eco-friendly, recycled and "green"; all these terms seem to positively influence the perception of millennials, increasing the reputation of the producer (Annunziata et al, 2019;Smith, 2010).…”
Section: Environmentally Friendly and Sustainable Food Consumptionmentioning
confidence: 99%
“…This result is in consonance with those found by other researchers [15,38,42,71,72], who reported that consumers show greater preferences for organic food products than for conventional ones. The standards of organic production are widely known to consumers [73], and Chen et al found that Chinese consumers are willing to pay for tomatoes carrying organic labels from different countries/regions [43]. We also examined the interaction effects between the Santong claim and organic certification and found substitution effects between them.…”
Section: Discussionmentioning
confidence: 95%
“…Esto da una idea de lo complejo que resulta definir la sostenibilidad, y por añadidura, que lo entiendan los ciudadanos. El consumo de alimentos es una de las áreas que más influye en la sostenibilidad ambiental, aunque muchos consumidores no son completamente conscientes de la asociación entre su consumo y el impacto ambiental de la producción de alimentos (Eldesouky et al 2020). Por ello, los cambios hacia pautas de consumo más sostenibles, junto con las innovaciones tecnológicas, deberían formar parte de la solución del problema de la sostenibilidad.…”
Section: Introductionunclassified
“…Sonoda et al, (2018) encuentran que casi el 90% de los consumidores estaban interesados y dispuestos a pagar por carne de ternera con etiqueta de bienestar animal o ecológico. Más recientemente Eldesouky et al, (2020) determinan que la mejor opción de compra para el consumidor sería la carne de vacuno ecológica, producida en España, con etiqueta de bienestar animal y ecológica. Sin embargo, y hasta donde llega el conocimiento de estos autores, no se ha investigado el interés de los consumidores por carne procedente de ganado trashumante ni los aspectos de garantía que podría proporcionar un certificado que acreditase esta procedencia.…”
Section: Introductionunclassified
See 1 more Smart Citation